Mismatch Responses to Speech Contrasts in Preschoolers with and without Developmental Language Disorder - Ana Campos; Jyrki Tuomainen; Outi Tuomainen (Brain Sciences, 2023)
This study compared cortical responses to speech in preschoolers with typical language development (TLD) and with Developmental Language Disorder (DLD). We investigated whether top-down language effects modulate speech perception in young children in an adult-like manner. We compared cortical mismatch responses (MMRs) during the passive perception of speech contrasts in three groups of participants: preschoolers with TLD (n = 11), preschoolers with DLD (n = 16), and adults (n = 20). We also measured children’s phonological skills and investigated whether they are associated with the cortical discrimination of phonemic changes involving different linguistic complexities. The results indicated top-down language effects in adults, with enhanced cortical discrimination of lexical stimuli but not of non-words. In preschoolers, the TLD and DLD groups did not differ in the MMR measures, and no top-down effects were detected. Moreover, we found no association between MMRs and phonological skills, even though the DLD group’s phonological skills were significantly lower. Our findings suggest that top-down language modulations in speech discrimination may not be present during early childhood, and that children with DLD may not exhibit cortical speech perception deficits. The lack of association between phonological and MMR measures indicates that further research is needed to understand the link between language skills and cortical activity in preschoolers.